MOLECULAR INVESTIGATIO OF HEAT SHOCK PROTEIN 70 (HSP70) EXPRESSION LEVELS IN ASPERGILLLOSIS PATIENTS - Al-Barazanchi , Taqwa A.; Abood , Z. H.; Al-rawi, R. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Forty nine sputum specimens were collected from patients with aspergillosis attended to four hospitals in Baghdad. The frequent species of Aspergillus identified included Aspergillus fumigatus 23(46.9%), Aspergillus niger 14 (28.6%), followed by Aspergillus flavus 12 (24.5%). According to age group factor, the age group (50-59) years appeared to be more susceptible to infected by aspergillosis with percentage at (24.5%). The results was revealed that no significant differences between male and female with aspergillosis infection. To detect A.fumigatus isolates by molecular methods, the genomic DNA were extracted and amplification to detect the aspHS gene by the singleplex PCR method using species-specific primers for these A.fumigatus, to sum up 17 of isolates from 23 isolates of A.fumigatus which identified the previous by morphological and microscopic methods, by observing the singleplex PCR product of aspHS gene with 108 bp. The total RNA of A.fumigatus was extracted by using TRIzol purification kit and convert to cDNA and submit for further amplification to detect the Heat Shock protein 70 genes (Hsp70 genes) expression as virulence factor in variable temperature activation include 28 ºC, 37 ºC and 45 ºC by real time PCR. The results of HSP70 gene expression showed the level increased at 37 ˚C but decreased when the temperature increases to 45 ˚C.